Anthony Crosland on Equity and State - Reisman, David A. (Journal of Income Distribution®, 1998)
Anthony Crosland, Oxford economist and Labour Party politician, developed a sophisticated approach to Britain’s mixed economy and post-war welfare state in The Future of Socialism and other writings. This paper examines has theory of redistribution and citizenship in order to establish why he assigned to the State responsibility for producing a greater equality both for opportunity and of outcome than was possible under the free market order. In respect of opportunity, Crosland looked to State education, public housing and income maintenance for the liberalization of potential that would make the selective process of competitive capitalism into a genuinely fair race. In respect of the outcome, Crosland wanted to level finishes and not simply starts in the case of wealth, power and culture that were for him the architects of intolerable social distance. The paper concludes with an evaluation of Crosland’s theory and proposals.